FOREIGN DIRECT INVESTMENT: DIAGNOSIS AND PROPOSALS FOR A PUBLIC POLICY AGENDA FOR BRAZIL - de Abreu Campanário, Milton; Muniz da Silva, Marcello; de Freitas Chagas Junior, Milton; Cesarino Pessoa, Leonel (Internext, 2012)
The research analyses the viability to adopt policies to enhance Brazilian Foreign Direct Investment FDI. Based on statistical data and on literature review, the policy agenda frames the underling questions surrounding FDI. There is not yet a theoretical framework to deal with emergent countries economic outward FDI. There exist strong evidences that capital flows through FDI generate externalities in the following domains: macroeconomic, international trade, and microeconomic (in themes closed related to industrial organization and innovation). The theoretical proposition has its grounds in the conception that international capital flows are absolutely compatible in the following contexts: monetary, commercial, industrial organization and innovation policies. A better positioning of national enterprises internationally may result in growing partnership within the foreign environment. Brazil has not yet a set of policies to deal with inward and outward Brazilian FDI flows, without necessarily jeopardizing macroeconomic policy and the related monetary and currency stabilization goals. Summing up, it is contended that FDI stimulus by means of public policies may contribute not just to a better competitiveness and innovation of Brazilian enterprises but also to assure balanced growing and economic structural change.